Electrochemical Reduction of CO2 at Coinage Metal Nanodendrites in Aqueous Ethanolamine. Issue 4 (15th December 2020) - Hossain, M. Nur; Ahmad, Syed; da Silva, Iranaldo Santos; Kraatz, Heinz‐Bernhard
Abstract: Electrocatalytic reduction of CO2 into usable chemicals is a promising path to address climate change and energy challenges. Herein, we demonstrate the synthesis of unique coinage metal (Cu, Ag, and Au) nanodendrites (NDs) via a facile galvanic replacement reaction (GRR), which can be effective electrocatalysts for the reduction of CO2 in an ethanolamine (EA) solution. Each metal ND surface was directly grown on glassy‐carbon (GC) substrates from a mixture of Zn dust and the respective precursor solution. The electrocatalytic activities of the synthesized ND surfaces were optimized for CO2 reduction in EA solution by varying their composition. It was determined that a 0.05 mol fraction of EA exhibited the highest catalytic activity for all metal NDs. Linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) techniques showed that metal‐ND electrodes possessed higher current densities, lower onset potentials and lower charge‐transfer resistances for CO2 reduction than their smooth polycrystalline electrode counterparts, indicating improved CO2 reduction catalytic activity. It was determined, using FTIR and NMR spectroscopy, that formate was produced as a result of the CO2 reduction. Abstract : Dendrites to the front : Cu, Ag, and Au nanodendrites are directly grown on a glassy‐carbon substrate via a facile galvanic replacement reaction. They can be used as effective electrocatalysts for the reduction of CO2 in an ethanolamine solution.